Effect of situational factors on store format choice behaviour in food and grocery retailing in India: Multiple discriminant analysis - Cherukuri Jayasankaraprasad (IBSU Scientific Journal (IBSUSJ), 2010)
A shopping situation is a particular act of buying behaviour occurring at a specific point in space and time. The purpose of this paper is to examine the impact of situational factors such as task definition, perceived risk, physical surroundings, social surroundings and temporal aspects on retail format choice decisions relating to kirana stores, convenience stores supermarkets and hypermarkets in the fast growing food and grocery retailing in India. The study is purely based on primary data collected from 1040 retail customers through mall intercept method using structured and non-disguised questionnaire from sixty different food and grocery stores from twin cities of Secunderabad and Hyderabad in Andhra Pradesh in India. The multiple discriminant analysis reveals that physical surroundings (ambience, store design and visual merchandising), task definition (regular purchase, purchase in large quantities and getting ideas/knowing new products), perceived risk (time, financial, and physical), temporal aspects (time spent and convenient timing hours), and social interactions and experiences have significant affect on supermarket and hypermarket store format choice decisions. Whereas, task definition (regular purchase and urgent purchase), perceived risk (performance, financial, psychological and physical) and convenient timing hours have significant effect on kirana store and convenience store formats. The findings would help the retailers to better understand the effect of situational variables on consumers retail format choice behaviour in food and grocery and, as a consequence, to undertake more effective retail marketing strategies for competitive advantage. Given the absence of published academic literature and empirical findings relating to store format choice behaviour in grocery retailing in India, this study is relevant to retail marketers in terms of format development and reorientation of marketing strategies.
Keywords: 330; consumer behaviour; task definition; perceived risk; physical surroundings; temporal aspects; social surroundings; grocery retailing; India